Ionic liquids modified Cu3(PO4)2 hybrid nanoflower for dehydrogenase immobilization by biomimetic mineralization. (October 2022) - Xiang, Xiaoyan; Xiong, Yu; Zhang, Qian; Lei, Hangbin; Liu, Kailong; Wang, Shizhen
Abstract: Ionic liquid modified organic-inorganic hybrid materials were applied for the immobilization of thermophilic and halophilic phenylalanine dehydrogenase from Natranaerobius thermophiles (NTAaDH). Biosynthesis of L -homophenylalanine by asymmetric reductive amination was studied. ILs modification induced the formation of nanoflowers with different morphologies. The activity of Cu3 (PO4 )2 -[EMIM]BF4 -NTAaDH was 1.92-fold of Cu3 (PO4 )2 -NTAaDH, which indicated activity enhancement of ionic liquid modification. The correlation between the logP value of organic solvents and the activity of immobilized enzyme showed that high logP value increased the activity of enzyme. The effect of ionic liquid on the morphology of immobilized enzyme particles was studied by SEM. Mechanism of ionic liquids modification was investigated by multi-level interactions between the enzyme and carrier, and the cage effects enhanced enzyme stability. Ionic liquids modified organic-inorganic hybrid materials have excellent biocompatibility and conductivity, and are expected to expand the application in biocatalysis. Graphical Abstract: Synthesis mechanism of Cu3 (PO4 )2 -[EMIM]BF4 -NTAaDH. ga1 Highlights: Fine-tuning the microenvironment of nanoflower by ionic liquids enhanced enzyme activity and stability. Activity of Cu3 (PO4 )2 -[EMIM]BF4 -NTAaDH was 1.92-fold of Cu3 (PO4 )2 -NTAaDH. Organic solvent with high LogP value enhanced immobilized enzymes activity. ILs modified nanoflower with biocompatibility and conductivity is expected for biocatalysis.